Been Coming through Some Hard Times : Race, History, and Memory in Western Kentucky - Glazier, Jack (Book collections on Project MUSE., 2012)
This book is a study of race and racism across two centuries in the hinterland of the upper South. Its implications are at once depressingly familiar and distinctly fresh. From the earliest days when slaves were brought to western Kentucky, the descendants of both slaves and slave owners in Hopkinsville, Kentucky, have continued to inhabit the same social and historic space. Part ethnography and part historical narrative, this book offers a penetrating look at this southern town and the surrounding counties, delving particularly into the ways in which its inhabitants have remembered and publicly represented race relations in their community. Neither Deep South nor Appalachian, this western Kentucky borderland presented unique opportunities for African American communities and also deep, lasting tensions with powerful whites. The author conducted fieldwork in Hopkinsville for some ten months, examining historical evidence, oral histories, and the racialized hierarchy found in the final resting places of Black and white citizens. His analysis shows how structural inequality continues to prevail in Hopkinsville. The book's ethnographic vignettes of worship services, school policy disputes, segregated cemeteries, a "dressing like our ancestors" day at an elementary school, and Black family reunions poignantly illustrate the ongoing debate over the public control of memory. Ultimately, the book critiques the lethargy of white Americans who still fail to recognize the persistence of white privilege and therefore stunt the development of a truly multicultural society. The author's personal investment in this subject is clear. The book began as an exploration of the life of James Bass, an African American who settled in Hopkinsville in 1890 and whose daughter, Idella Bass, cared for the author as a child. Her remarkable life profoundly influenced the author and led him to investigate her family's roots in the town. This personal dimension makes the author's ethnohistorical account especially nuanced and moving. Here is a uniquely revealing look at how the racial injustices of the past impinge quietly - but insidiously - upon the present in a distinctive, understudied region.